2007
DOI: 10.1152/ajprenal.00005.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A induces senescence in renal tubular epithelial cells

Abstract: The nephrotoxic potential of the widely used immunosuppressive agent cyclosporine A (CsA) is well recognized. However, the mechanism of renal tubular toxicity is not yet fully elucidated. Chronic CsA nephropathy and renal organ aging share some clinical features, such as renal fibrosis and tubular atrophy, raising the possibility that CsA may exert some of its deleterious effects via induction of a stress-induced senescent phenotype. We investigated this hypothesis in HK-2 cells and primary proximal tubular ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 39 publications
2
89
0
Order By: Relevance
“…4B). These findings are compatible to the previous finding of H 2 We then examined whether ROS, as induced by toxic compounds or direct exposure of H 2 O 2 , was the cause of the increased p21 expression and cell cycle arrest in L-PDMCs, since this has been reported previously (16,22). However, we found that NAC inhibition of H 2 O 2 accumulation had no effect on cell cycle arrest (Fig.…”
supporting
confidence: 91%
“…4B). These findings are compatible to the previous finding of H 2 We then examined whether ROS, as induced by toxic compounds or direct exposure of H 2 O 2 , was the cause of the increased p21 expression and cell cycle arrest in L-PDMCs, since this has been reported previously (16,22). However, we found that NAC inhibition of H 2 O 2 accumulation had no effect on cell cycle arrest (Fig.…”
supporting
confidence: 91%
“…Because YB-1 is important in preventing premature senescence, which has been demonstrated in YB-1 knockdown mice (44), a diminished YB-1 content may cause an impaired proliferation. This is in line with the observations in renal tubular epithelial cells, in which CsA mediates cell cycle arrest (45) and enhanced senescence (46), potentially mediated by YB-1 depletion.…”
Section: Discussionsupporting
confidence: 92%
“…Premature senescence was observed in renal cells under conditions of high glucose, oxidative stress, or ischemia reperfusion injury (17,18,35). p21 and p16 pathways are very important signaling pathways of premature senescence in renal inherent cells (23).…”
Section: Discussionmentioning
confidence: 99%